Regulation of Hematopoietic Stem Cell Activity by Inflammation - Schuettpelz, Laura; Link, Daniel (Frontiers in Immunology, 2013)
Hematopoietic stem cells (HSCs) are quiescent cells with self-renewal capacity and the ability to generate all mature blood cells. HSCs normally reside in specialized niches in the bone marrow that help maintain their quiescence and long-term repopulating activity. There is emerging evidence that certain cytokines induced during inflammation have significant effects on HSCs in the bone marrow. Type I and II interferons, tumor necrosis factor, and LPS directly stimulate HSC proliferation and differentiation, thereby increasing the short-term output of mature effector leukocytes. However, chronic inflammatory cytokine signaling can lead to HSC exhaustion and may contribute the development of hematopoietic malignancies. Pro-inflammatory cytokines such as G-CSF can also indirectly affect HSCs by altering the bone marrow microenvironment, disrupting the stem cell niche and leading to HSC mobilization into the blood. Herein, we review our current understanding of the effects of inflammatory mediators on HSCs, and we discuss the potential clinical implications of these findings with respect to bone marrow failure and leukemogenesis.